Characterization of some representative soils from the Ganges floodplain of Bangladesh (Dhaka University Journal of Biological Sciences, 2012)
DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11519Dhaka Univ. J. Biol. Sci. 21(2): 201-205, 2012 (July)